Effect of the deep cryogenic treatment on the stress corrosion cracking behaviour of AA 2017‐T4 aluminium alloy. Issue 5 (9th December 2015) - Cabeza, M.; Feijoo, I.; Merino, P.; Trillo, S.
Abstract : This paper will focus on the effect of deep cryogenic treatment (DCT) on the microstructure, mechanical properties and stress corrosion cracking susceptibility of a heat‐treated aluminium alloy. The different microstructures have been characterized by X‐ray diffraction, optical microscope, scanning electron microscope and transmission electron microscope. The stress corrosion cracking susceptibility of the alloy, before and after the DCT, in chloride solution was examined using slow strain rate test (SSRT) method at various strain rates. The results show that the sub‐zero treatment increases the secondary non‐coherent nanoparticles at the grain boundary, and this slight precipitation did not produce any modification of the mechanical properties. Furthermore the compressive residual stresses of the material were higher after than before the treatment. Both these effects are the responsible for an improvement of the stress corrosion cracking behaviour of this alloy after DCT.